2020
DOI: 10.1515/znc-2020-0192
|View full text |Cite
|
Sign up to set email alerts
|

Design and synthesis of novel n-butyphthalide derivatives as promising botanical fungicides

Abstract: In order to obtain novel botanical fungicides, three series of novel 6-substituted n-butyphthalide derivatives have been designed and synthesized via nucleophilic addition, reduction, nitrification, amination, sulfonation, Sandmeyer and Suzuki reaction. The mycelium growth rate method was used to evaluate the inhibition activity against eight phytopathogenic fungi in vitro. Preliminary bioassay tests showed that compounds 6f, 6n, 6p, 6r and 7a exhibited better activity for some fungi at 50 μg/mL than the posit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 18 publications
(16 reference statements)
0
3
0
Order By: Relevance
“…In the previous study, we found that 3-n-butylphthalide (NBP), an active ingredient derived from celery seed and capable of treating ischemic stroke, had potential antifungal potency against phytopathogenic fungi. [3][4][5][6] Thus, it can serve as a precursor for the development of new botanical fungicide. Moreover, among the family of fivemembered nitrogen/oxygen-containing aromatic heterocycles, 1,3,4-oxadiazole and 1,2,4-triazole scaffolds are widely present in pharmaceutical or pesticide molecules, and exhibited a pronounced diversity of biological activities due to their ability to form interactions with various enzymes, proteins, and receptors in organisms, [7][8][9] such as anticancer, [10,11] antiviral, [12,13] antibacterial, [14][15][16] antifungal, [17][18][19] and herbicidal [20] activities (Figure 1).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the previous study, we found that 3-n-butylphthalide (NBP), an active ingredient derived from celery seed and capable of treating ischemic stroke, had potential antifungal potency against phytopathogenic fungi. [3][4][5][6] Thus, it can serve as a precursor for the development of new botanical fungicide. Moreover, among the family of fivemembered nitrogen/oxygen-containing aromatic heterocycles, 1,3,4-oxadiazole and 1,2,4-triazole scaffolds are widely present in pharmaceutical or pesticide molecules, and exhibited a pronounced diversity of biological activities due to their ability to form interactions with various enzymes, proteins, and receptors in organisms, [7][8][9] such as anticancer, [10,11] antiviral, [12,13] antibacterial, [14][15][16] antifungal, [17][18][19] and herbicidal [20] activities (Figure 1).…”
Section: Introductionmentioning
confidence: 99%
“…Natural products are still one of the effective ways to explore novel pesticides with high efficiency, low toxicity, and environmental friendliness. In the previous study, we found that 3‐n‐butylphthalide (NBP), an active ingredient derived from celery seed and capable of treating ischemic stroke, had potential antifungal potency against phytopathogenic fungi [3–6] . Thus, it can serve as a precursor for the development of new botanical fungicide.…”
Section: Introductionmentioning
confidence: 99%
“…Botanical pesticides are an emerging component of modern pesticide development (Coman et al 2013;Zhao et al 2022;Ngegba et al 2022). Recently, secondary metabolites, such as organic acid, alkaloids and phytosterol, have been used as the main active ingredients of new botanical pesticides, which are biodegradable, economical and environmentally friendly (Luo et al 2021;Li et al 2022;Chen et al 2011a, b). The application of plant extracts as the main active compounds of pesticides to control fungal diseases has a promising prospect.…”
Section: Introductionmentioning
confidence: 99%